2023
DOI: 10.1186/s40168-023-01638-3
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbes exacerbate systemic inflammation and behavior disorders in neurologic disease CADASIL

Sheng Liu,
Xuejiao Men,
Yang Guo
et al.

Abstract: Background Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a cerebral small vessel disease that carries mutations in NOTCH3. The clinical manifestations are influenced by genetic and environmental factors that may include gut microbiome. Results We investigated the fecal metagenome, fecal metabolome, serum metabolome, neurotransmitters, and cytokines in a cohort of 24 CADASIL patients with 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Recently, a pioneering study shed light on the disruption of the normal metabolic rhythm of the gut microbiome in host mammals with a high-fat diet, indicating a potential link between the gut pathobiome and diseases caused by extrinsic factors [ 40 ]. A study suggested that the gut pathobiome could exacerbate systemic inflammation and behavioral disorders in the neurological disease CADASIL [ 41 ]. However, the causality between the gut pathobiome and host diseases, especially upon exposure to emerging biotoxin pollution, remained largely unexplored and elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a pioneering study shed light on the disruption of the normal metabolic rhythm of the gut microbiome in host mammals with a high-fat diet, indicating a potential link between the gut pathobiome and diseases caused by extrinsic factors [ 40 ]. A study suggested that the gut pathobiome could exacerbate systemic inflammation and behavioral disorders in the neurological disease CADASIL [ 41 ]. However, the causality between the gut pathobiome and host diseases, especially upon exposure to emerging biotoxin pollution, remained largely unexplored and elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in the normal gut microbiome have been associated with the development of various chronic diseases, including cerebrovascular diseases (Liu et al, 2023), obesity (Liu et al, 2017) and diabetic nephropathy (Zhang et al, 2022). Regulating or reshaping gut microbiota is crucial for host health.…”
Section: Discussionmentioning
confidence: 99%
“…A LDA score (log10) of 2.0 was selected as the cutoff to indicate significantly enriched taxa. It was assessed whether a combined microbial biomarker could effectively differentiate between CKD and control groups using random forest models, which evaluates the significance of every feature by measuring the increase in classification errors when permuted (Liu et al, 2023). Furthermore, The ROC curve is used to evaluate the performance of a classifier by plotting the curve of true positive rate (sensitivity) and false positive rate (1-specificity) varying with the threshold and calculating metrics such as the area under the curve (AUC).…”
Section: Microbial Community Taxonomic and Functional Profilingmentioning
confidence: 99%
“…HE staining of the intestinal tissue verified its pathological changes. The inflammatory factors in the blood have a direct impact on the level of inflammation in the brain, meanwhile also regulated by the level of intestinal inflammation ( Wang et al, 2022 ; Liu et al, 2023 ). Therefore, the expression levels of inflammatory factors in serum and brain tissue of each group were further detected.…”
Section: Discussionmentioning
confidence: 99%